2021
DOI: 10.1002/eat.23477
|View full text |Cite
|
Sign up to set email alerts
|

Emotional eating across different eating disorders and the role of body mass, restriction, and binge eating

Abstract: Objective Different subtypes of eating disorders (ED) show dysfunctional eating behaviors such as overeating and/or restriction in response to emotions. Yet, systematic comparisons of all major EDs on emotional eating patterns are lacking. Furthermore, emotional eating correlates with body mass index (BMI), which also differs between EDs and thus confounds this comparison. Method Interview‐diagnosed female ED patients (n = 204) with restrictive (AN‐R) or binge‐purge anorexia nervosa (AN‐BP), bulimia nervosa (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 68 publications
6
28
1
2
Order By: Relevance
“…When feeling negative, women with OW and patients with BN ate much more than usual, whereas women with UW and patients with AN were more likely to eat much less than usual. These findings were consistent with studies that reported under-eating during negative emotional states in AN (Baños et al, 2014;Meule et al, 2021;Reichenberger et al, 2021) and UW groups (Geliebter & Aversa, 2003), and emotional overeating in women with obesity. However, in their study, the UW, NW, OW and obesity groups, as well as the ED groups, had a wider age range and more people in their late twenties or early 30s in the higher BMI group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When feeling negative, women with OW and patients with BN ate much more than usual, whereas women with UW and patients with AN were more likely to eat much less than usual. These findings were consistent with studies that reported under-eating during negative emotional states in AN (Baños et al, 2014;Meule et al, 2021;Reichenberger et al, 2021) and UW groups (Geliebter & Aversa, 2003), and emotional overeating in women with obesity. However, in their study, the UW, NW, OW and obesity groups, as well as the ED groups, had a wider age range and more people in their late twenties or early 30s in the higher BMI group.…”
Section: Discussionsupporting
confidence: 92%
“…For eating disorders (EDs), people with bulimia nervosa (BN) employed emotional eating as an accessible yet dysfunctional strategy when experiencing negative emotions they could not regulate effectively, which led to binge eating (Evers et al., 2010), while those with anorexia nervosa (AN) ate less than usual when in negative moods (Meule et al., 2021). In non‐ED populations with different weights, higher BMI was associated with higher levels of emotional eating (Geliebter & Aversa, 2003; Reichenberger et al., 2021). Although the link between negative emotions and overeating or binge eating has been documented in populations with obesity or with EDs across many studies, there have been few studies in underweight populations.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…The variation in subscale scores was also prominent among responses to items relating to the EPR subscale, which contains items that are referring to emotional eating, and eating without physical cues of hunger. Individuals with AN spectrum disorders scored highly on the EPR subscale, which was not a surprising finding given that individuals with AN generally have lower scores on emotional eating when compared with other eating disorder diagnoses [38]. As noted above, individuals with binge eating behaviours disorders scored low on this subscale, which is characteristic of this diagnosis, given strong links between mood intolerance and bulimic pathology [29].…”
Section: How Do Persons With Different Ed Diagnoses Differ In Intuitive Eating?mentioning
confidence: 73%
“…Different analytical approaches might be combined to fully exploit the potential of such time-series data analyses, both in a data-driven as well as theory-based way. Future applications to other populations, e.g., individuals with eating disorders, might reveal clearer ‘patterns’ of relationships between affective states and eating behaviour [ 56 ] and may also help to modify existing theories and develop novel ones.…”
Section: Discussionmentioning
confidence: 99%